Chromosome analysis and morphometric of croslet horseshoe bat, Rhinolophus coelophyllus and least horseshoe bat, Rhinolophus pusillus (Chiroptera, Rhinolophidae) - Isara Patawang (2018)
© 2017 The Japan Mendel Society. Chromosome and morphometric analyses of the croslet horseshoe bat (Rhinolophus coelophyllus) and least horseshoe bat (R. pusillus) from Northeast of Thailand were studied. Bat chromosome preparations were conducted by squash technique from bone marrow and testis. Conventional staining and Ag-NOR banding techniques were applied to stain the chromosomes. The results showed that the diploid chromosome number of R. coelophyllus and R. pusillus were 2n=62, and the fundamental number (NF) were 64 in both species. The types of autosomes observed were 26 large telocentric, 12 medium telocentric, and 22 small telocentric chromosomes in R. coelophyllus and R. pusillus. The X-chromosome was a largest acrocentric chromosome and the Y-chromosome was a small acrocentric chromosome in both species. NORs are located at the secondary constriction near the centromere on the long arm of the large acrocentric chromosome pair 13 in R. coelophyllus and R. pusillus. We found that during metaphase I the homologous chromosomes showed synapsis, which can be defined as 31 bivalents. Six external morphological characters were measured as well as 13 cranial and dental measurements. The karyotype formulae were as follows: Rhinolophus coelophyllus; 2n(62) = L 26 t + M 12 t + S 22 t + sex chromosomes Rhinolophuspusillus; 2n(62) = L 26 t + M 12 t + S 22 t + sex chromosomes.